Beyond "living fossils": Can comparative genomics finally reveal novelty?. (28th August 2021) - Sanchez, Gustavo; Simakov, Oleg; S. Rokhsar, Daniel
Abstract : Cephalopods have recently moved into the research focus due to the growing number of sequenced genomes, molecular tools, and laboratory culture (Albertin & Simakov, 2020)⁠. Genome data now allows us to ask how the many known novelties of cephalopod morphology are reflected in their genomes and gene regulation. A crucial gap in this understanding has been the limited information for the Nautilus, the last survivor of a cephalopod lineage that diverged from the highly derived coleoid clade (octopus, squid, cuttlefish) around 400 million years ago. The publication of Nautilus genomes (in this issue of Molecular Ecology [Huang et al., 2021; Zhang et al., 2021])⁠ will help us understand which genetic changes happened when, and ultimately how they contributed to cephalopod evolution.